KEPUASAN KERJA SEBAGAI MEDIASI: KARAKTERISTIK PEKERJAAN, KEDISIPLINAN KERJA, KINERJA PEGAWAI - wardasari amalia; muryati muryati; survival survival (BADAN PENERBITAN UNIVERSITAS WIDYAGAMA, 2021)
ABSTRACT This study explains the effect of job characteristics and work discipline on employee performance mediated by job satisfaction. The population is all employees of the Public Library and Regional Archives of Malang City, both those with civil servant status and non-civil servant employees, totaling 63 people. The sampling method in this study used